2010
DOI: 10.1002/jctb.2515
|View full text |Cite
|
Sign up to set email alerts
|

UV photocatalytic oxidation of paint solvent compounds in air using an annular TiO2-supported reactor

Abstract: BACKGROUND: One of the most important industrial sources of volatile organic compounds (VOCs) is related to coating and painting applications. In this sense, photocatalytic oxidation can become an innovative and promising alternative for the remediation of air polluted by VOCs. In this study the UV photodegradation of m-xylene, toluene and n-butyl acetate, as representative compounds of paint solvents, was carried out in an annular reactor using a TiO 2 -glass wool supported catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
18
1
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
8
18
1
3
Order By: Relevance
“…At high inlet concentrations, the reaction rate, which determined the number of molecules degraded 9 in a given time, became constant and independent of the inlet concentration (as can be observed and discussed in the next section). observed at different air gaps and air flow rates (Fig 3a) for isovaleraldehyde degradation, which was similar to results previously described for aromatic and oxygenated compounds [29]. For both compounds, a nearly complete elimination (RE > 90%) was observed for low IL values, while at high inlet loads, the EC remained relatively constant at a maximum EC of 12 mg C m for isovaleric acid.…”
Section: Effects Of Inlet Concentration and Flow Rate On Voc Degradationsupporting
confidence: 89%
See 2 more Smart Citations
“…At high inlet concentrations, the reaction rate, which determined the number of molecules degraded 9 in a given time, became constant and independent of the inlet concentration (as can be observed and discussed in the next section). observed at different air gaps and air flow rates (Fig 3a) for isovaleraldehyde degradation, which was similar to results previously described for aromatic and oxygenated compounds [29]. For both compounds, a nearly complete elimination (RE > 90%) was observed for low IL values, while at high inlet loads, the EC remained relatively constant at a maximum EC of 12 mg C m for isovaleric acid.…”
Section: Effects Of Inlet Concentration and Flow Rate On Voc Degradationsupporting
confidence: 89%
“…For both compounds, a nearly complete elimination (RE > 90%) was observed for low IL values, while at high inlet loads, the EC remained relatively constant at a maximum EC of 12 mg C m for isovaleric acid. These values were comparable to those obtained previously in the removal of toluene and xylene [29]. The photocatalytic process can be modelled by Langmuir-Hinshelwood (LH) kinetics.…”
Section: Effects Of Inlet Concentration and Flow Rate On Voc Degradationsupporting
confidence: 88%
See 1 more Smart Citation
“…The results obtained for the UV 254 nm pre-treatment are in good agreement with those previously reported. 11 The biofilter unit that was used in the present study, including the filter material, had been used in a previous experiment for a period of more than 1 year to study the degradation of ethyl acetate and toluene.…”
Section: Methodsmentioning
confidence: 99%
“…Palau et al 11 obtained a maximum elimination capacity of 18 mg C m −3 s −1 in a continuous annular photoreactor for toluene and found the highest efficiency for humidified air. Most of the studies showed that almost complete mineralization of toluene to CO 2 and H 2 O occurred in the photocatalytic abatement of this contaminant.…”
mentioning
confidence: 98%